Structures of Marginalization: Examining Nepal’s Class, Caste, Gender, and Regional Inequalities (Panauti Journal, 2025)
Nepal’s development trajectory remains deeply uneven, shaped by enduring structural inequalities and the persistent marginalization of peripheral regions and vulnerable social groups. This article examines Nepal’s persistent underdevelopment by analyzing the intersecting dynamics of class, caste, gender, and geography. It critiques the Kathmandu-centric model of development, arguing that it has deepened regional disparities, particularly in marginalized areas such as Karnali and Sudurpaschim. Drawing on world-systems theory, internal colonialism, and feminist standpoint theory, the study reveals how entrenched structural inequalities manifest in unequal infrastructure, inadequate service delivery, labor exploitation, and political exclusion. Dalits, women, and other marginalized groups continue to face intersecting barriers, including systemic discrimination and limited access to education, healthcare, land, and financial services. Despite the introduction of decentralization and inclusive policies, elite dominance and bureaucratic resistance hinder the realization of equitable development. Using secondary sources and thematic analysis, the article highlights that reliance on remittances, tokenistic political inclusion, and uneven access to services reflect deeper systemic failures. It calls for a transformative, justice-oriented development approach that amplifies marginalized voices and ensures the redistribution of power, resources, and representation to address Nepal’s socio-spatial inequalities.